Need Analysis of Pre-Braille Skills Module as The Pedagogical Support in Early Braille Literacy Learning - Lee, Alya Qasdina Ng Ai; Hock, Kway Eng (South Asian Journal of Social Sciences and Humanities, 2023)
Pupils with visual impairments adapt in a variety of ways, one of which is learning to "see" through touch. Therefore, tactual readiness is essential for them to have access to physical reading materials. However, conventional instructional methods emphasize on memorising braille codes and braille writing rather than tactile reading. As a result, pupils find reading braille materials physically less engaging, and in the worst possible case, these pupils suffer from academic deficiencies as a consequence of their inability to read tactile information. This will substantially reduce their prospects of success in the future. As a corollary, instructional strategies emphasising interventions to enhance tactile sensitivity are necessary for resolving this issue. On the basis of the discrepancy model, a questionnaire was created to identify whether teachers need specific interventions to suit the special educational needs of pupils with visual impairments, particularly during early braille learning lessons. This questionnaire was distributed randomly to 92 special education teachers who taught visually impaired pupils in a variety of special education programs (PPK) in Malaysia.Beforehand, seven experts were recruited to evaluate the content validity of the need analysis instrument, and an S-CVI value of 0.86 was determined. In the meanwhile, eleven experts evaluated the instrument’s face validity; the S-FVI was 0.90. Meanwhile, the quantitative items in this questionnaire had an alpha value greater than.70, indicating that the instrument used is appropriate for obtaining responses from the intended group, since the instrument’s alpha value surpassed >.07 and remained within the recommended range for good internal consistency, that could be interpreted as reliable. According to the results, all of the respondents claimed they need a comprehensive module for pre-braille skills that includes step-by-step instructions and video demonstrations. In essence, teachers need a guided module to implement pre-braille skill interventions that foster tactile awareness and tactile perception to support early braille development among pupils with visual impairment in schools and homes.